2016
DOI: 10.1111/1744-7917.12279
|View full text |Cite
|
Sign up to set email alerts
|

Spruce budworm feeding and oviposition are stimulated by monoterpenes in white spruce epicuticular waxes

Abstract: Monoterpenes, source of the distinctive odor of conifers, are generally considered plant defensive compounds. However, they are also known to act as long-range insect attractants, as they are volatile and permeate forest airspaces. Moreover, they are lipid soluble and can be absorbed into plant epicuticular waxes. We test their role in short-range host plant choice by both adult females and larvae of a folivorous forest pest (Choristoneura fumiferana). We conducted laboratory assays testing the responses of Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…White spruce has evolved some resistance to spruce budworm herbivory (Lamara et al, 2018;Mageroy et al, 2015), and this is reflected in the population genetic structure of the tree (Méndez-Espinoza et al, 2018;Parent et al, 2017). Spruce budworm behavior has changed in the presence of its host plants or some of their components (e.g., waxes and sugars) (Albert, 1991;Daoust et al, 2010;Ennis, Despland, Chen, Forgione, & Bauce, 2017), indicating that it has evolved adaptive, genetically driven traits associated with herbivory.…”
Section: Introductionmentioning
confidence: 99%
“…White spruce has evolved some resistance to spruce budworm herbivory (Lamara et al, 2018;Mageroy et al, 2015), and this is reflected in the population genetic structure of the tree (Méndez-Espinoza et al, 2018;Parent et al, 2017). Spruce budworm behavior has changed in the presence of its host plants or some of their components (e.g., waxes and sugars) (Albert, 1991;Daoust et al, 2010;Ennis, Despland, Chen, Forgione, & Bauce, 2017), indicating that it has evolved adaptive, genetically driven traits associated with herbivory.…”
Section: Introductionmentioning
confidence: 99%
“…Advantage 2: Eliminates the Effects of Tissue Quality It has been well documented that insects feed differentially based on the physical and chemical attributes of plant material [58][59][60][61], and therefore another major challenge associated with the use of true herbivory is the differential feeding patterns likely to be observed between treatments. Ryalls et al [58] showed that high concentrations of foliar silicon reduced herbivore feeding compared to leaves with lower amounts of silicon.…”
Section: Advantages Of Simulated Herbivorymentioning
confidence: 99%
“…Indeed, in our study, correlations between previous-year foliage wax in July 2010 and current-year needles in May 2011 show no significant values for any of the monoterpenes (data not shown). Previous work shows that ovipositing female budworm moths are attracted to monoterpene emissions (Grant et al 2007) and use wax monoterpenes as a cue for host identification (Ennis et al 2015). Similarly, ovipositing sawflies use wax monoterpenes to determine between different pine species that offer varying D r a f t quality foliage to offspring (Kazlauskas et al 2011).…”
Section: Functional Role Of Foliar Monoterpenesmentioning
confidence: 99%
“…It appears that both constitutive and induced monoterpenes are important in defense against several xylophages (Huber et al 2004, Keeling and Bohlmann 2006, Keeling 2016. Several monoterpenes, notably δ-3-carene and bornyl acetate, have been suggested to be toxic to the spruce budworm at high concentrations (Kumbasli andBauce 2013, Fuentealba andBauce 2012). Monoterpenes are also known to be active against fungi and gram-negative bacteria (Novak et al 2014), and could protect against pathogens both at the leaf surface and within leaf airspaces (Martin et al 2003).…”
Section: Functional Role Of Foliar Monoterpenesmentioning
confidence: 99%
See 1 more Smart Citation